2017
DOI: 10.21043/thufula.v4i1.1939
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pembelajaran :Taksonomi Bloom Dalam Games Simulation Method Di Tingkat Raudhatul Athfal

Abstract: <p>Penelitian ini bertujuan untuk mendeskripsikan strategi pembelajaran:<em>games simulation method</em>(metode simulasi permainan) menggunakan taksonomi Bloom. Pengajaran bahasa untuk anak usia dini memegang peranan penting dalam perkembangan bahasanya. Strategi pembelajaran yang digunakan untuk membuat anak didik merasa senang dan tanpa beban adalah dengan <em>games simulation method. </em>Taksonomi Bloom adalah alat bagi pendidik untuk mengembangkan kemampuan bahasa secara ters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Policies and models of behavior for literacy learning activities during the Covid-19 pandemic are carried out through playing activities, telling stories and conducting simple experiments or experiments both while children are studying at home and while children are participating in limited face-toface learning activities. This is in line with what was said by Pancaningrum (2015) stated that we as adults must be able to respect children's rights, one of which is their desire to learn something. Just as when children want to learn to read and write, we can offer them some activities they like.…”
Section: A Policies and Models Of Literacy Learning Behavior During T...supporting
confidence: 90%
“…Policies and models of behavior for literacy learning activities during the Covid-19 pandemic are carried out through playing activities, telling stories and conducting simple experiments or experiments both while children are studying at home and while children are participating in limited face-toface learning activities. This is in line with what was said by Pancaningrum (2015) stated that we as adults must be able to respect children's rights, one of which is their desire to learn something. Just as when children want to learn to read and write, we can offer them some activities they like.…”
Section: A Policies and Models Of Literacy Learning Behavior During T...supporting
confidence: 90%
“…In line with these findings, Wahyuni (2017) revealed that the development of Anderson and Krathwolh's Taxonomy on thinking skills could be used to determine the extent of students' thinking skills in solving problems. Meanwhile, Pancaningrum (2016;Filtri & Sembiring, 2018) suggested that the categories of knowledge, analysis, synthesis, and evaluation domains were very well provided with certain learning strategies. Furthermore, in these findings, students at the early childhood level could build their vocabulary and mindset (Rohmah & Waluyo, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Referring to [10] [11][12] [13][21] as our basis, we map the objectives to the game contents or actions. Note that the sample actions in Table 1 can be created either before or after the game design has been created.…”
Section: A Embedding the Board Game Design With Conservative Organiza...mentioning
confidence: 99%